Toxicity of selected neonicotinoid insecticides against Phenacoccus solenopsis infesting ornamental hibiscus plants (Zoo Botanica, 2025)
The cotton mealybug, Phenacoccus solenopsis, poses a significant threat to economically important crops. Insecticide application is an effective and quick method for pest control and stresses continuous search for number of insecticides to be available for alternate use. Current research focuses the toxicity comparison of acetamiprid, imidacloprid, clothianidin, thiamethoxam and emamectin benzoate using leaf dip method under controlled laboratory conditions. Among these, clothianidin exhibited the highest toxicity with LC50 values of 0.26 and 0.19 ppm after 72 hours for Rawalpindi and Islamabad populations, respectively. Thiamethoxam followed with LC50 of 0.41 and 0.49 ppm for these populations, respectively. Emamectin benzoate, however, was the least toxic. This study suggests neonicotinoids like clothianidin and thiamethoxam for effective mealybug management.
Keywords: Toxicity; Phenacoccus solenopsis; chemical insecticides; leaf dip method; neonicotinoids